Requirements for the activation of sustainable schools at the primary level in Almadinah Almunawwarah - Al- Johani, Badriah Ayed Awwad; Al- Saysi, Areej Hamza (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify requirements for the activation of sustainable schools at the primary level in Almadinah. So it used both quantitative and qualitative measures. And applied the questionnaire on a random sample of 181 female leaders and 364 teachers, while the interview was applied to a sample of 7 sustainability experts. The results of the quantitative data showed that sustainability is applied in intermediate schools in Al- Madinah Al- Munawara. The social dimension ranked first. the results of the interviews have presented a set of requirements needed for initiating sustainable schools and some obstacles to the application. The human resources requirements were represented by the need for senior leaders who adopt the concept of sustainability and its goals together with sustainability coordinators at schools. The study then concluded with the construction of a proposed vision for initiating sustainable schools that are expected to contribute to the sustainability of the community (150).